2023
DOI: 10.7759/cureus.36377
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Disorder Treated With Chiropractic Therapy

Abstract: Temporomandibular disorders (TMDs) are common and affect the temporomandibular joint (TMJ) and surrounding musculoskeletal tissues. Although traditional rehabilitative treatments such as physiotherapy, occlusal splints, orthodontics, and electrotherapy effectively manage TMDs, chiropractic therapy is emerging as a promising non-invasive treatment option. We report a 39-year-old female patient with TMD who underwent chiropractic therapy, including spinal adjustments, soft tissue therapy, and exercise rehabilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Lidocaine, which blocks voltage-gated Na+ channels ( 72 ); NSAIDs, which inhibit cyclooxygenase in peripheral tissue ( 73 ); opioids, which also have peripheral targets ( 74 ); botulinum toxins, which can act at the neuromuscular junction, autonomic ganglia, postganglionic parasympathetic nerve endings, and postganglionic sympathetic nerve endings ( 75 ); are all drugs that inhibit the transfer of pain from the periphery to the central nervous system. Physical therapy, including, but not limited to thermal ultrasound, chiropractic therapy, craniomandibular therapy, and exercise rehabilitation ( 76 , 77 ), have been shown to partially and/or completely remedy symptoms in some forms of TMD excluding systemic or whiplash-related TMD ( 78 , 79 ). The effectiveness of these peripheral treatments indicates that a portion of TMD cases associated with pain may stem from somatosensory activation (e.g., nociceptors).…”
Section: Current Treatment Approaches For Pain In Temporomandibular D...mentioning
confidence: 99%
“…Lidocaine, which blocks voltage-gated Na+ channels ( 72 ); NSAIDs, which inhibit cyclooxygenase in peripheral tissue ( 73 ); opioids, which also have peripheral targets ( 74 ); botulinum toxins, which can act at the neuromuscular junction, autonomic ganglia, postganglionic parasympathetic nerve endings, and postganglionic sympathetic nerve endings ( 75 ); are all drugs that inhibit the transfer of pain from the periphery to the central nervous system. Physical therapy, including, but not limited to thermal ultrasound, chiropractic therapy, craniomandibular therapy, and exercise rehabilitation ( 76 , 77 ), have been shown to partially and/or completely remedy symptoms in some forms of TMD excluding systemic or whiplash-related TMD ( 78 , 79 ). The effectiveness of these peripheral treatments indicates that a portion of TMD cases associated with pain may stem from somatosensory activation (e.g., nociceptors).…”
Section: Current Treatment Approaches For Pain In Temporomandibular D...mentioning
confidence: 99%
“…Chiropractors in Hong Kong utilize manual techniques such as spinal manipulation and soft tissue mobilization to address musculoskeletal dysfunction and reduce pain [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. According to a 2013 survey undertaken by the Census and Statistics Department of the Hong Kong Special Administrative Region, more than half (53.6%) of the 33,700 individuals who received chiropractic care had previously tried other forms of treatment.…”
Section: Chiropractic As An Effective and Low-risk Therapymentioning
confidence: 99%
“…[3] Chiropractors in Hong Kong are legally authorized to diagnose and treat musculoskeletal conditions. As conservative spine specialists and primary care practitioners, numerous studies have reported that chiropractors in Hong Kong provide non-invasive care for prevalent neuromusculoskeletal conditions and injuries [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. However, their inability to officially certify patients' incapacity limits the utility of chiropractic services.…”
Section: Introductionmentioning
confidence: 99%